Trends in Contemporary Business Decision-making: A review of literature and suggestions for further research - Krauss, Yaron (Marketing & Menedzsment, 2019)
Decision-making has been considered as a prominent function of executives ever since C.l. Barnard’s 1930s classic work on management [Barnard 1968; Bazerman 1998]; yet recently it has gained an added significance in light of the risky market conditions [Hammond, Keeney and Raiffa 1998], and the technological innovations characterizing the contemporary economic reality [Mullins 2002]. These conditions make the sustaining of the competitive edge and the attainment of the position of “the leader of the pack” [Cook 1998] a complex task indeed for all industries, from banking [Crone 1995] to hi-tech [Frick & Torres 2002].